Penerapan Sanksi Pidana Sesuai Ketentuan KUHP Terhadap Pelaku Aborsi - Yolanda Hendartin; Achmad Zulfikar Siregar (Jurnal Sosial Politik dan Hukum, 2024)
This study aims to analyze the application of criminal sanctions in accordance with the provisions of the Criminal Code (KUHP) against abortion perpetrators in Indonesia. Abortion, which is defined as the termination of a pregnancy before the fetus is capable of living outside the womb, is unlawful except under certain conditions provided for by law. This research uses normative juridical methods with a statutory approach and case analysis. Data was collected through literature studies and related legal documents. The purpose of making this article is to contain the responsibility of perpetrators of abortion acts that are not in accordance with ARTICLE 75 PARAGRAPH (2) OF LAW NUMBER 36 OF 2009 CONCERNING HEALTH. The results showed that the application of criminal sanctions against abortion perpetrators depends largely on the circumstances and conditions behind the act, as well as the judge's interpretation of the applicable law. In addition, the study found a need to clarify and update legal provisions related to abortion in order to increase legal certainty and fairness. It is hoped that the results of this research can contribute to the development of criminal law in Indonesia related to handling abortion cases.